Linear and zosteriform lichen planus in a tertiary care centre: a case series - Neerja Puri; Neetu Verma; Sukhmani Kaur Brar (International Journal Of Community Medicine And Public Health, 2023)
Lichen planus (LP) is a common mucocutaneous condition, but its distribution in a zosteriform and linear pattern is rare. Zosteriform LP is a rare variant with dermatomal distribution and can occur at trauma prone sites. Linear distribution of the disease has been described in less than 1% of patients. Treatment options are topical corticosteroids and systemic antihistamines. We hereby present a case series of four cases with linear and zosteriform patterns in which the biopsy findings were corroborative of lichen planus. In the first case report of a 25-year-old female presented to dermatology OPD of tertiary health Centre with hyperpigmented patches confined to left half of trunk, left arm and left leg for 6 months. Brownish black macules involving left breast and adjoining back and abdomen were seen in zosteriform pattern. In the second case report, a 25-year-old male presented for evaluation of hyperpigmented raised and pruritic lesion over the right axilla of 5 months’ duration Third case was of a 26-year-old female patient who presented with pruritic violaceous macules on left leg extending from mid part of leg to medial aspect of knee and medial side of thigh in a discontinuous pattern for last 3 years. A 34-year-old female presented with history of pruritic rash over the left side of trunk in the fourth case report. The case series is rare and hence being reported.